Relations of King Władysław Jagiełło of Poland with the Latin Kingdom of Cyprus in the Early 1430s - Burkiewicz, Łukasz (Études sur la Région Méditerranéenne, 2023)
The article is devoted to a relatively unknown Polish-Cypriot episode in the late medieval period, which was unusual for the realities of 15th century Europe. In 1426, Cyprus was conquered by the Egyptian-Syrian Mamluk Sultanate, and the island’s ruler himself, Janus of Lusignan, was taken captive by the Muslims. After regaining his freedom, the Cypriot king attempted to acquire aid in the Christian world to throw off Muslim supremacy. One such attempt was the expedition of a Cypriot envoy to Poland in 1432. The proposal made by the Cypriots on that occasion was for the marriage of the heir to the island’s throne with Hedwig, the daughter of Poland’s King Władysław Jagiełło, and also included a request for a loan in exchange for the Polish side’s almost practical assumption of control over Cyprus.